(untitled) (Advancements in Homeopathic Research, 2026)
Background: India is the second largest producer of tomato in the world. Farmers increase the quantity than the quality by using the fertilizers like synthetic nitrogen; it in turn causes hazardous effect on environment & humans. The result of this study provides potential benefits of using Homoeopathic Medicines in plant growth & quality parameters. Objectives: To compare the both Homoeopathic medicines Silicea Terra & Sulphur, in quality parameters of Solanum Lycopersicum. Methods: Six fields are used for our study, each field measures 32m2. In each field, 25 numbers of plants are planted. Field A crop – Silicea Terra 6C, Field B crop – Silicea Terra 30C, Field C crop – Sulphur 6C, Field D crop – Sulphur 30C, Field E crop - Synthetic Nitrogen Fertilizer as Standard control, Field F crop - Placebo control. Results: Crops treated with Homoeopathic medicine Silicea Terra 6C, Sulphur 30C has significant effect in height of plant when compare to Standard & Placebo Control. Before study NPK analysis of Soil reports as Low Fertility Soil. Tomato yield seen only in crops treated with Homoeopathic medicines. Silicea 6C field tomatoes have increased nutritive value than normal referral level. Normal referral